Low-level laser therapy: Characteristics of clients treated at the Clinical Podiatrics servisse (Research, Society and Development, 2021)
Objective: To describe and analyze the characteristics of clients undergoing low-level laser therapy followed up in a Clinical Podiatrics service. Method: Descriptive, retrospective and documentary study, carried out in a Clinical Podiatrics service in the State of Rio de Janeiro, from January 2019 to January 2020. 110 medical records of clients treated at the service were analyzed. Results: It was identified that 322 low-intensity laser therapy sessions were carried out over a 12-month period, with an average of 3 applications per client. There was a prevalence of females (60%), and the age group of 50 and 69 years (54%). The main podiatric diagnoses were onychomycosis (75%); pedis (15%) and wounds (5%). Regarding comorbidities, 29% had arterial hypertension; 17% dyslipidemia; and 6% obesity. Conclusion: The study provided knowledge about the clinical characteristics of the studied sample. It is recommended that further studies be carried out to disseminate knowledge in the areas of Laser Therapy and Clinical Podiatrics that are still embryonic in Brazil.